Advanced signature functionalities from the code equivalence problem. Issue 2 (3rd April 2022) - Barenghi, Alessandro; Biasse, Jean-François; Ngo, Tran; Persichetti, Edoardo; Santini, Paolo
Abstract : The LESS signature scheme, introduced in 2020, represented a fresh start for code-based signatures. In this paper we explore advanced functionalities for signature schemes, stemming from the work of LESS. First, we adapt a recent protocol of Beullens et al. to obtain a construction for (linkable) ring signatures. Then, we realize an identity-based signature scheme following the traditional approach by Joye and Neven. Our performance numbers confirm that signature schemes based on the code equivalence problem have considerable potential for practical applications.